Description of the pupa and additional characters of the fourth-instar larva, female, and male genitalia of Uranotaenia (Uranotaenia) coatzacoalcos Dyar & Knab, with keys for the identification of Mexican species of Uranotaenia (Diptera: Culicidae) - Rivera-García, Karina D.; Rísquez-Pérez, Abril; Ibáñez-Bernal, Sergio (Zootaxa, 2019)
Eleven species of Uranotaenia, one belonging to the subgenus Pseudoficalbia and ten to the subgenus Uranotaenia, have been recorded in Mexico. In general, two species are commonly recorded in urban areas by the vector surveillance programs, but the other species are rarely collected as they occupy habitats in non-anthropized environments, and for that reason they remain poorly known. Some of the species recorded in Mexico have not been described in the pupal stage and other developmental stages have only been partially described, making their recognition difficult. One of these species is Uranotaenia (Uranotaenia) coatzacoalcos Dyar & Knab, as a complete description of its larval chaetotaxy is not available, and the pupa has not been described. In this report, we provide a complete morphological description of the fourth-instar larva, the first description of the pupa, and a review of the female and male diagnostic characteristics useful for recognition of the species. We also provide keys in English and Spanish for the recognition of the larvae, pupae, females, and male genitalia of the species of Uranotaenia recorded in Mexico.